The Rule of Law Under the Constitution of Nepal - Giri, Saroj Kumar (Gyanjyoti, 2023)
This article deals with the constitutional provisions of rule of law, its implementation status and challenges to implement it. Rule of law is the value of democratic institution that focuses on the legal justification of every action by the government officials and adjudication of disputes through the independent and competent court. The Constitution has guaranteed the rule of law through its preamble, fundamental rights with constitutional remedy, directive principle and state policies and various other provisions that have added hope for the people of limited government. The Constitution focuses on both horizontal and vertical separation of state power. Horizontal power is divided into three organs of government; legislative, executive and judiciary and vertical power is divided into central, provincial and local level government with the federal character of the nation. The judiciary is empowered to test the constitutionality of legislative and administrative actions which is the essence of rule of law of democratic nations. The Constitution guarantees the functional and institutional independence of judiciary. Thus, the article argues that the Constitution of Nepal, 2015 wants to establish, promote and protect the rule of law in Nepal but its implementation depends on the commitment and actions of the state authority. The finding of the study is there is the need of more laws and institutional arrangements to establish rule of law and to implement Constitution. The analysis is significant to as it helps to understand the constitutional provision of rule of law, its implementation status and challenges to implement.